Developing an Effective Team-Based Emergency Training Program for Medical Students - Hartono, Pinter; Adiyanto, Bowo; Nur, Rifdhani Fakhrudin; Ancilla, Cornelia; Rahma, Aulia Zuhria (Faculty of Medicine-Universitas Airlangga, 2024)
Introduction: Team-based patient management in critical care demands a knowledgeable, skillful, and responsive doctor who collaborates well on teams. Medical education is responsible for producing competent graduates who meet the above requirements. However, the current medical curriculum in Indonesia tends to focus only on individual knowledge and appraisal. There was no standardized university-based group emergency training and examination with comprehensive emergency topics beyond cardiac and trauma cases. Objective: This study aimed to develop and evaluate a team-based emergency training program that enhances medical students' preparedness and teamwork skills in dealing with future emergencies in the workplace. Methods: We developed Acute Life Threatening Events Management (ALTEM), a three-day emergency training program consisting of pre-test, lectures, guided skill practice, group (case-based) simulation exam, and post-test. Group simulation occurred in a virtual hospital with high-fidelity mannequins, actual medical equipment (i.e., beds, monitors, drugs, tools, pads), two-way mirror rooms, and simulated patient family to resemble real hospital situations. The program was then evaluated by a modified Kirkpatrick evaluation model, which measures individual perception, satisfaction, understanding, and performance related to the program. Results: A total of 114 participants were involved in this study. Most subjects (>80%) had a good experience with the program. ALTEM training program significantly increased communication and teamwork (p <0.001) and decision-making towards critical patients (p <0.001) in the univariate analysis. Communication and teamwork remained related considerably in the multivariate analysis (aOR 7.866; p = 0.005). Conclusion: The ALTEM simulation program obtained a good response from the subjects and was a prospective program to improve medical students' competence and teamwork skills in emergencies.